Schools as Transformation Centers: The Role of Schools in Shaping the Golden Generation - Siregar, Nurliani; Jamaludin, Jaja; Sahrul, Sahrul; Abdullah, Abdullah; Lele, David Moto (MSJ : Majority Science Journal, 2025)
This article aims to analyze the role of schools in providing comprehensive education, both from academic and non-academic aspects, in order to form individuals who excel in various fields. The research method used is Systematic Literature Review (SLR), which aims to identify, evaluate, and synthesize the results of previous research related to this topic. The SLR approach allows researchers to gain a comprehensive understanding of educational strategies and practices that have proven effective in shaping the golden generation. The articles used in this study were selected based on their high quality and relevance to the focus of the research. The results of the study show that schools play a role not only in academic mastery but also in the development of students' character and social skills. Academically, the school equips students with science, cognitive skills, and critical and creative thinking abilities through relevant curricula and innovative learning methods. The use of technology in education also contributes to increasing students' adaptability to changing times. Meanwhile, from a non-academic aspect, schools function as a place for character formation through various extracurricular activities that teach the values of discipline, responsibility, leadership, and empathy. In addition, social interaction in the school environment also forms communication and cooperation skills that are important for community life and the world of work